Dietary and pharmacological treatment of abdominal pain in IBS. Issue 5 (23rd February 2017) - Camilleri, Michael; Boeckxstaens, Guy
Abstract : This review introduces the principles of visceral sensation and appraises the current approaches to management of visceral pain in functional GI diseases, principally IBS. These approaches include dietary measures including fibre supplementation, low fermentable oligosaccharides, disaccharides, monosaccharides and polyols diet, and pharmacological approaches such as antispasmodics, peppermint oil, antidepressants (tricyclic agents, selective serotonin reuptake inhibitors), 5-HT3 receptor antagonists (alosetron, ondansetron, ramosetron), non-absorbed antibiotic (rifaximin), secretagogues (lubiprostone, linaclotide), μ-opioid receptor (OR) and κ-OR agonist, δ-OR antagonist (eluxadoline), histamine H1 receptor antagonist (ebastine), neurokinin-2 receptor antagonist (ibodutant) and GABAergic agents (gabapentin and pregabalin). Efficacy and safety are discussed based on pivotal trials or published systematic reviews and meta-analysis, expressing ORs or relative risks and their 95% CIs. Potential new approaches may be based on recent insights on mucosal expression of genes, and microRNA and epigenetic markers in human biopsies and in animal models of visceral hypersensitivity. The objectives of this review are to appraise the physiology and anatomy of gut sensation and the efficacy in the relief of visceral pain (typically in IBS) of several classes of therapies. These include fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAPs) and different classes of medications (box 1 ).